Protective effects of ulinastatin and methylprednisolone against radiation-induced lung injury in mice. (30th September 2016) - Sun, Yu; Du, Yu-Jun; Zhao, Hui; Zhang, Guo-Xing; Sun, Ni; Li, Xiu-Jiang
Abstract: The effectiveness of ulinastatin and methylprednisolone in treating pathological changes in mice with radiation-induced lung injury (RILI) was evaluated. Forty C57BL/6 female mice received whole-chest radiation (1.5 Gy/min for 12 min) and were randomly allocated into Group R (single radiation, n = 10), Group U (ulinastatin treatment, n = 10), Group M (methylprednisolone treatment, n = 10), or Group UM (ulinastatin and methylprednisolone treatment, n = 10). Another 10 untreated mice served as controls (Group C). Pathological changes in lung tissue, pulmonary interstitial area density (PIAD) and expression levels of transforming growth factor β1 (TGF-β1) and tumor necrosis factor α (TNF-α) in lung tissue, serum and bronchoalveolar lavage fluid were determined. Alleviation of pathological changes in lung tissue was observed in Groups U, M and UM. Treatment with ulinastatin, methylprednisolone or both effectively delayed the development of fibrosis at 12 weeks after radiation. Ulinastatin, methylprednisolone or both could alleviate the radiation-induced increase in the PIAD ( P < 0.05 or P < 0.01). Treatment with ulinastatin, methylprednisolone or both significantly reduced the expression of TNF-α, but not TGF-β1, at 9 weeks after radiation compared with Group R ( P < 0.01). Ulinastatin and / or methylprednisolone effectively decreased the level of TNF-α in lung tissue after RILI and inhibited both the inflammatory response and the development of fibrosis.